New Solutions for the Resonant Nonlinear Schrödinger Equation with Anti-Cubic Nonlinearity - Aslan, Ebru Cavlak; Gürgöze, Leyla (My University, 2023)
In this work, the Resonant nonlinear Schrödinger equation (RNLSE) with anti-cubic nonlinearity is considered. The Jacobi elliptic function method (JEFM) has been employed on the RNLSE. The many new forms of dark, dark-bright, singular, combo-singular, bright-singular solitons and periodic solutions for governing model are reached. Furthermore, the graphics of solutions are presented.
Keywords: Soliton; NLSE; Optical soliton